Acceptability and intention of purchase of tomato-based sauces in the GAM, Costa Rica - Víquez Ramírez, Nicole Valeria (2023)
The objective of this work was to evaluate the acceptance and purchase intention of an Italian tomato-based sauce from a small company and three commercial brands. The research was carried out under a quantitative approach, using a transectional experimental design, through a sensory evaluation and a structured survey applied to 101 consumers in the Greater Metropolitan Area. A randomized complete block design was used, and the means of the different sauces were compared for four intrinsic attributes, smell, flavour, colour, and texture. Additionally, principal component analysis (PCA) was used to identify the sensory attributes underlying the differences between the four tomato sauces evaluated, and cluster analysis was used to perform a segmentation of consumers. Finally, the determinants of the decision to purchase a sauce were analysed using a probit model. Among the results, significant differences could be observed for all attributes. In addition, two consumer profiles were formed and the most influential factor of the purchase decision was flavour.